Production of aflatoxin on rice - Ömer Demet; Halis Oğuz; İlhami Çelik; Ferhan Nizamlıoğlu (Eurasian Journal of Veterinary Sciences)
In this study, the production of aflatoxin at a grade appropriate for dietary anatoxin feeding studies were performed under our laboratory conditions. After sporufation of Aspergillus parasiticus NRRL 2999 strain in the tubes containing Sabouraud Dextrose Agar (SDA), the spores were removed by washings with 0.005 % Triton X-100 {Merck) and an enriched suspension of spores were obtained. Following determination ol the spore numbers in per ml. of suspension, the suspension was used to inoculate the sterilized rice In erlenmeyer flasks and after inoculation the flasks were in to an incubator for fermentation at 28 "C. At first stage of the study, thirlylour erlenmeyer flasks were fermented. On the 2nd day of fermentation lour erlenmeyers were removed because thai rice kernels formed a large compact mass After seven days fermentation, aflatoxin levels of the (lasks were determined by Fiuorescence Spectrophotometry. The mean aflatoxin level of thirty flasks was approximately 62.71 mg/kg (ppm). At second stage, three groups of erlenmeyers each having six ones, were fermented for 6,9, and 12 days. Aflatoxin levels were determined as follows; 30, 16 mg/kg. 29 65 mg/kg and 29.58 mg/kg respectively. Observation of no increase after 6 th day of the fermentation. As a result, 62.71 mg/kg total aflatoxin level were produced on rice, provides a sufficient amount for dietary aflatoxin feeding studies.